Optimizing solar dish performance using analytical flux distribution in focal region - Dany Iman Santoso; Bambang Antoko; Djatmiko Ichsani (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
In this paper, thermal performance analysis of 4 m2 solar dish collector is presented.The focal image characteristics of the solar dish are determined to propose the suitable design of a receiver. A flat plate was used for the receiver to measure flux distribution in the focal region. The measurement had been done in the midday. Intercept factor based on this distribution had been calculated and was obtained to calculate thermal efficiency after total heat loss was described. From the experiment, total heat loss was formed by conductive and radiative in the receiver. The results showed that the increase in total heat loss followed the increase in receiver temperature and it caused a decrease in thermal efficiency. On the peak of the measurement or in midday, receiver temperature can achieve 138°C and it gave around 1200-Watt heat loss and it was dominated by radiative heat loss for around 80%. The thermal efficiency of the system due to flux distribution measurement in the focal region was above 70% and it was classified as high average but we needed to cover this flux up so it did not lose a lot of heat. Cavity aperture would keep around 20% total heat loss and it minimized radiative heat loss from the flux. The design of cavity aperture was the next discussion to insulate thermal heat reflection of the parabolic dish system from high radiative heat loss.©2020. CBIORE-IJRED. All rights reserved